ECONOMIC STATUS OF ARTISANAL FISHERMEN IN ONDO AND OGUN STATES, NIGERIA. - WILLIAMS, STELLA B. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The performance of the artisanal sector of Nigeria's fishing industry, accounted for between 96 percent in 1981 and 87 percent in 1984 of the total domestic fish productions. Primary data collected revealed that fishing costs were quite high in Ondo  State compared to Ogun State, estimates being N7,178 and N2,559 for Ondo and Ogun States respectively. Incomes estimated were from N1,850 to N15,200. Estimated averages were N12,097 and N3,944 for Ondo and Ogun States respectively. Fifty-six percent of the fishermen in the study area earned incomes between N1,300 and N2,900 annually. Incomes so obtained can be considered to be low for a family of seven. Thus, the fishermen engage in secondary occupation to supplement their incomes. Further studies are suggested to determine how to help the artisanal fishermen to achieve better fish catches that would result in higher income for them; and also, to determine the productivity of the artisanal fishermen and its impact on the national economy.